Participation in Cities in Sociological Discourse - A. A. Beschasnaya; N. N. Pokrovskaia (Дискурс, 2020)
Introduction. The social practice of participativeness, active participation in the transformation of urban space in the interests of residents, is gaining popularity among the urban population. The study of this phenomenon is interest for obvious integration with management decisions. Expanding the practice of implementing social activity of the population and studying the components of participativeness determine the goal of writing the paper-the formation of a theoretical and methodological basis for studying this phenomenon.Methodology and source. The paper presents a review of classical and modern sociological theories that reveal the potential of empirical study of aspects of the manifestation of participation of urban residents. Among the mentioned by the authors are the theory of social action, social solidarity, phenomenology, social constructivism.Results and discussion. The problematic nature of living in cities and the penetration of these problems into the daily interaction of citizens forms the origins of solidary participation of citizens-individual and private interests form collective actions-processes. Multiple individual forms of citizens' activity on urban improvement are transformed into participativeness – institutionalized joint activity. Its participants can take differentiated positions in the social structure of the urban community according to the criteria of having a diverse experience of interaction, i.e. exchange, with the urban environment and taking a position in the city management structure, which determines the level of regulated authority to make managerial decisions. The problems of urban life that are common to different categories of citizens and the typification of social activity to solve them order the interaction of participants, organize and “produce” the urban space.Conclusion. In the process of reasoning, a theoretical model of the formation of participativeness is presented, which allows us to trace the transformation of activity of the urban population into the right to the city and the formation of a favorable urban environment.